Activation of a Ca(2+)-permeable cation channel produces a prolonged attenuation of intracellular Ca(2+) release in Aplysia bag cell neurones - Magoski, Neil S (Blackwell Science Inc, 2000)
1. Brief synaptic stimulation, or exposure to Conus textile venom (CtVm), triggers an afterdischarge in the bag cell neurones of Aplysia. This is associated with an elevation of intracellular calcium ([Ca(2+)](i)) through Ca(2+) release from intracellular stores and Ca(2+) entry through voltage-gated Ca(2+) channels and a non-selective cation channel. The afterdischarge is followed by a prolonged (∼18 h) refractory period during which the ability of both electrical stimulation and CtVm to trigger afterdischarges or elevate [Ca(2+)](i) is severely attenuated. By measuring the response of isolated cells to CtVm, we have now tested the contribution of different sources of Ca(2+) elevation to the onset of the prolonged refractory period. 2. CtVm induced an increase in [Ca(2+)](i) in both normal and Ca(2+)-free saline, in part by liberating Ca(2+) from a store sensitive to thapsigargin or cyclopiazonic acid, but not sensitive to heparin. 3. In the presence of extracellular Ca(2+), the neurones became refractory to CtVm after a single application but recovered following ∼24 h, when CtVm could again elevate [Ca(2+)](i). However, this refractoriness did not develop if CtVm was applied in Ca(2+)-free saline. Thus, elevation of [Ca(2+)](i) alone does not induce refractoriness to CtVm-induced [Ca(2+)](i) elevation, but Ca(2+) influx triggers this refractory-like state. 4. CtVm produces a depolarization of isolated bag cell neurones. To determine if Ca(2+) influx through voltage-gated Ca(2+) channels, activated during this depolarization, caused refractoriness to CtVm-induced [Ca(2+)](i) elevation, cells were depolarized with high external potassium (60 mm), which produced a large increase in [Ca(2+)](i). Nevertheless, subsequent exposure of the cells to CtVm produced a normal response, suggesting that Ca(2+) influx through voltage-gated Ca(2+) channels does not induce refractoriness. 5. As a second test for the role of voltage-gated Ca(2+) channels, these channels were blocked with nifedipine. This drug failed to prevent the onset of refractoriness to CtVm-induced [Ca(2+)](i) elevation, providing further evidence that Ca(2+) entry through voltage-gated Ca(2+) channels does not initiate refractoriness. 6. To examine if Ca(2+) entry through the CtVm-activated, non-selective cation channel caused refractoriness, neurones were treated with a high concentration of TTX, which blocks the cation channel. TTX protected the neurones from the refractoriness to [Ca(2+)](i) elevation produced by CtVm in Ca(2+)-containing medium. 7. Using clusters of bag cell neurones in intact abdominal ganglia, we compared the ability of nifedipine and TTX to protect the cells from refractoriness to electrical stimulation. Normal, long-lasting afterdischarges could be triggered by stimulation of an afferent input after a period of exposure to CtVm in the presence of TTX. In contrast, exposure to CtVm in the presence of nifedipine resulted in refractoriness. 8. Our data indicate that Ca(2+) influx through the non-selective cation channel renders cultured bag cell neurones refractory to repeated stimulation with CtVm. Moreover, the refractory period of the afterdischarge itself may also be initiated by Ca(2+) entry through this cation channel.